2021
DOI: 10.3390/cells10102671
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intrahepatic Expression of Immune Checkpoint Molecules in Autoimmune Liver Disease

Abstract: Immune checkpoint molecules (ICM) are critical in maintaining immunologic homeostasis and participate in preventing or promoting autoimmune disease development. Exploring a large panel of intrahepatic inhibitory and stimulatory ICM is necessary for drawing a general picture of the immune alterations in autoimmune hepatitis (AIH). Here, we performed a multiparametric analysis of ICM, including PD-1, TIM3, LAG3, CTLA-4, OX40 and 4-1BB, and we determined their expression on intrahepatic lymphocyte subsets in untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It was not possible to explore the role of IS on hepatic B cells. Nonetheless, several groups clearly demonstrated that, by IHC, intrahepatic B cell numbers and or proportions decline sharply following IS ( 10 , 20 , 22 ), which was even bigger compared to the CD4 and CD8 cell number reductions. This may cause to question of whether or not B cells are incumbent as a “driver” in the pathogenesis of AIH ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was not possible to explore the role of IS on hepatic B cells. Nonetheless, several groups clearly demonstrated that, by IHC, intrahepatic B cell numbers and or proportions decline sharply following IS ( 10 , 20 , 22 ), which was even bigger compared to the CD4 and CD8 cell number reductions. This may cause to question of whether or not B cells are incumbent as a “driver” in the pathogenesis of AIH ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted to date, mostly on adults, to better understand how IS medications affect systemic and/or intrahepatic lymphocytes in patients with AIH (3,10,(20)(21)(22). Most notably, by means of immunohistochemistry (IHC), Diestelhorst et al noted a sharp decline (>50%) in intrahepatic Tregs proportions, following IS in children with AIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of T cells-mediated autoimmune responses against hepatocytes, in addition to alterations in the immune effects of T cells subsets, alterations in T cells immune checkpoints are also included. Detection in liver tissue of AIH patients not only observed aggregation of CD4 + and CD8 + T cells overexpressed by immune checkpoint PD-1 and 4-1BB, but also found that PD-1 + CD8 + T cells were strongly associated with disease activity and degree of liver injury in AIH patients rather than PD-1 + CD4 + T cells [ 90 ]. In addition, a study isolated circulating SLA-specific CD4 + T cells.…”
Section: Imbalance Of Liver Immune Microenvironment and Liver Diseasesmentioning
confidence: 99%
“…As interface hepatitis is a histological feature of AIH, pathogenic CD4 + T cells with autoantigen specificity are enriched in this lesion (10,11). Furthermore, there is a strong association between disease activity and abundance of liver infiltrating T cells (12). However, molecular mechanisms of activation and recruitment of T cells in AIH remain poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%